Direct Comparison of the Sensitivity of QCMs and AlN-based TFRs Biosensors. (2016) - Escolano, J.M.; Díaz-Durán, B.; Olivares, J.; Clement, M.; Mirea, T.; Iborra, E.
Abstract: We present the direct comparison of the performance of two gravimetric biosensors based on acoustic resonators, a quartz crystal microbalance and a high frequency AlN-based bulk acoustic wave film solidly mounted resonator (SMR). Both sensors are functionalized with streptavidin to detect the response to TBA29 aptamer biotin modified and different concentrations of thrombin. Experimental results reveal that both sensors succeed in detecting the targeted species, although SMRs show significantly greater sensitivity and a lower limit of detection.